Genetic cryptic demographic mode shift analysis in buffaloes of Odisha using STR markers shows an absence of recent bottleneck - Surarapu Lava Kumar; Ravinder Singh; Ankita Gurao; Shallu Saini; Vikas Vohra; Saket Kumar Niranjan; Monika Sodhi; Sushant Kumar Dash; Ranjit Singh Kataria (Journal of Livestock Biodiversity, 2025)
India is known for its livestock diversity, particularly in the buffalo population, which is highly diversified and the country is placed top among the buffalo rearing across the globe. Odisha state is home to exemplary and varied buffalo populations, featuring prominent breeds and populations like Chilika, Kalahandi, Paralakhemundi, Sambhalpuri, and the latest registered breed, Manda. It is intriguing to know if some rare alleles are contributing to the survival and adaptability of Odisha buffalo breeds in the niche, which is generally hostile to other Indian buffalo breeds. The data already generated using a set of 20 highly polymorphic heterologous markers on 192 animals of Chilika, Kalahandi, Paralakhemundi and Sambhalpuri buffalo populations was analyzed for the current study. The mutation drift equilibrium analysis for buffalo populations revealed no significant heterozygosity excess, when evaluated using three different models of evolution viz. infinite alleles model (IAM), step-wise mutation model (SMM) and two-phase model (TPM). The buffalo populations, few of them being small in size, still did not show significant heterozygosity excess under any of the three models of microsatellite evolution, thus indicating the absence of any recent genetic bottleneck. Mode shift analysis displayed a normal L-shaped curve which is indicative of the absence of any recent past bottleneck. The results of the present study will help formulate rational breeding strategies as well as the conservation of unique germplasm of Odisha buffaloes. Key words: Bottleneck, Buffaloes, Mutation drift equilibrium, Odisha